Neurosurgery Residency Training and beyond in Turkey: A National Survey Study - Korkmaz, Taha Şükrü; Çetintaş, Semih Can; Akkaya, Süleyman; Toklu, Süreyya (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Training neurosurgery specialists is a challenging and demanding process. This national survey study was conducted to evaluate the infrastructure of neurosurgery residency programs and training clinics in Turkey and to assess how these factors impact specialist practice.A national survey consisting of 32 questions was distributed to neurosurgeons who had been practicing as specialists for at least two years. The survey was divided into four sections: demographic information, residency training process, hospital where they currently work as specialists, and microsurgical experience. Statistical analyses, including chi-square and logistic regression, were conducted to examine factors influencing surgical performance in specialist practice.Regression analyses indicated that performing skin-to-skin surgeries during residency significantly and most effectively increased the likelihood of performing these procedures as a specialist. Additionally, working in anatomy laboratories, attending hands-on cadaver courses, and increased years of practice were all positively associated with surgical performance. It was also found that participants who graduated within the last 5 years were statistically significantly less likely to have attended hands-on courses or visited another clinic for observerships/fellowships compared with those who graduated more than 5 years ago.Findings suggest that neurosurgical training in Turkey is affected by disparities in clinical infrastructure and hands-on experience. Standardizing residency experiences and ensuring access to necessary equipment and training resources could enhance neurosurgical competency and consistency in specialist practice.
Keywords: neurosurgery; neurosurgical residency; turkey; training; survey